Vulvoperineal Hidradenitis Suppurativa: Diagnosis, Treatment, and Management of Deformities. Issue 10 (October 2021) - Ogunleye, Adeyemi A.; Ndem, Idorenyin E.; Bui, Helen; Sayed, Christopher J.
Abstract : Importance: Hidradenitis suppurativa (HS) is a chronic, inflammatory disorder affecting skin of intertriginous areas that is often encountered and treated by nondermatologic specialists. Objective: The purpose of this literature review is to provide a comprehensive, clinical source of information on HS as it relates to incidence of disease, pathophysiology, diagnosis, and overall management of this condition. Evidence Acquisition: Sources were obtained through a comprehensive literature search using PubMed and PMC. Various terms were used to query the database, including "hidradenitis suppurativa, " "pathogenesis, " "prevalence, " "management, " "surgery, " "perineal, " and "vulva." Results: Underreported prevalence and unknown pathogenesis have subsequently led to variable approaches in clinical management, often employing a combination of medical and surgical management. Conclusion: Early diagnosis and treatment of HS may lead to better disease control and minimize patients' associated morbidity related to disease. Relevance: Knowledge of vulvoperineal hidradenitis is necessary for gynecologists and primary care physicians to ensure early diagnosis, management, and referral for optimal patient outcomes. Target Audience: Obstetricians and gynecologists, family physicians. Learning Objectives: After completing this activity, the learner should be better able to describe the presentation and staging of hidradenitis suppurativa; explain possible medical and surgical treatments; and identify options for correction of vulvar deformities.